In Situ Assembly of Ordered Hierarchical CuO Microhemisphere Nanowire Arrays for High‐Performance Bifunctional Sensing Applications. Issue 6 (30th April 2021) - Dai, Tiantian; Deng, Zanhong; Fang, Xiaodong; Lu, Huadong; He, Yong; Chang, Junqing; Wang, Shimao; Zhu, Nengwei; Li, Liang; Meng, Gang
Abstract: Seeking a facile approach to directly assemble bridged metal oxide nanowires on substrates with predefined electrodes without the need for complex postsynthesis alignment and/or device procedures will bridge the gap between fundamental research and practical applications for diverse biochemical sensing, electronic, optoelectronic, and energy storage devices. Herein, regularly bridged CuO microhemisphere nanowire arrays (RB‐MNAs) are rationally designed on indium tin oxide electrodes via thermal oxidation of ordered Cu microhemisphere arrays obtained by solid‐state dewetting of patterned Ag/Cu/Ag films. Both the position and spacing of CuO microhemisphere nanowires can be well controlled by as‐used shadow mask and the thickness of Cu film, which allows homogeneous manipulation of the bridging of adjacent nanowires grown from neighboring CuO hemispheres, and thus benefits highly sensitive trimethylamine (TMA) sensors and broad band (UV–visible to infrared) photodetectors. The electrical response of 3.62 toward 100 ppm TMA is comparable to that of state‐of‐the‐art CuO‐based sensors. Together with the feasibility of in situ assembly of RB‐MNAs device arrays via common lithographic technologies, this work promises commercial device applications of CuO nanowires. Abstract : A novel methodology of in situ assembly of regularly bridged CuO microhemisphere nanowire arrays (RB‐MNAs) devices by thermal oxidation of ordered Cu hemisphere arrays prepared by dewetting and evaporating patterned Ag/Cu/Ag films has been demonstrated. Bifunctional sensing of the RB‐MNAs device exhibits much better sensing performance toward both trimethylamine molecules and UV–vis–IR light.